Flipbook on Indonesian cultural diversity to enhance learning outcomes for fourth graders - Hilda Kusumaningtyas; Ali Sunarso (Universitas Muhammadiyah Malang, 2024)
Researchers have conducted observations at SDN Denanyar 3 Sragen and obtained problematic results, namely limited learning media and low student learning outcomes in Social Sciences subjects. This study aims to develop, test the feasibility, and effectiveness of the learning media Flipbook Indonesian Cultural Diversity. The type of method used in this research is Research and Development (R&D) with the Bord and Gall development model which has 10 steps and researchers only use 9 steps. The validity test of the product being developed was carried out by material and media expert lecturers as examiners of the learning media